Rhodopsin kinase: Expression in mammalian cells and a two-step purification - Bruel, Christophe (The National Academy of Sciences, 2000)
A suitable system for expression of the rhodopsin kinase (RK) gene and its mutants is needed for structure–function studies of RK. Previously, investigation of the baculovirus system showed satisfactory production of RK, but posttranslational isoprenylation was deficient. We now report on a comparative study of expression of the RK gene in yeast (Pichia pastoris), COS-1 cells and in an HEK293 stable cell line. Expression in COS-1 cells, by using pCMV5 vector, is the most satisfactory. A two-step procedure for purification of the expressed enzyme with an N-terminal histidine tag has been developed. The purified enzyme has correct posttranslational modifications and shows a somewhat broader pH vs. catalytic activity profile than the wild-type enzyme.